Impact of the change in household dietary patterns on CO2 emissions in Japan - Eun, Sungtae (Frontiers in Environmental Economics, 2022)
Japan is a country committed to complying with the international agreement on mitigating greenhouse gases (GHGs) causing climate change. However, the 2011 Tohoku Earthquake and Tsunami in March 2011 led the country had to modify the energy and environmental policy to global warming. The 15 m of tsunami occurred from an underwater earthquake hit the east coast where the nuclear reactors were located. The coolant system failed and the radioactive materials were spread out into the atmosphere, ocean, and soil. The Japanese government investigated the level of contaminated materials (iodine, cesium, etc.) and reassessed the food safety regulations. Simultaneously, consumers' anxiety about the food system was increasing and their preferences for food consumption were affected by the food safety phenomenon that arose in connection with the nuclear accident after the natural disaster. Japanese consumers avoided agricultural and fish products originating from the land and sea, so the consumption per capita of fish decreased by 11.3% while the beef consumption increased by 13.7% between 2011 and 2020. As reported by the Food and Agriculture Organization (FAO), meat and dairy products are accounted for around 16.5% of global GHGs emissions per year, and there are differences in the emission factors between beef (40.5 kgCO2e/kg) and fish (7.7 kgCO2e/kg). Per capita meat and fish consumption in Japan affected the GHGs emissions and the study employs the Synthetic Control Method (SCM) to estimate the impact of a change in dietary patterns on CO2 emissions from household food consumption. The outcome variable is CO2 emissions from household food consumption and the intervention period is between 1995 and 2019 (pre-intervention: 1995–2010; post-intervention: 2011–2019). Analyzing 32 countries, placebo studies, leave-one-out, and post-/pre-MSPE ratio are performed to make the statistical inferences. The results present that there is a meaningful relationship between the dietary patterns and the increase in CO2 emissions. Unlike the countries in the control group, Japan shows a significant increase in CO2 emissions from household food consumption after the natural disaster. However, the westernization of the diet can be another long-term factor affecting climate change. Therefore, future research can involve analyzing the impact of CO2 emissions from household food consumption in multiple treated countries with multiple interventions.